Estudo de localização de unidades de atendimento para os acidentes de trânsito - Mendes, Lourival Gomes (2011)
Traffic accidents (TA) have assumed high numbers, registering a large amount of dead, wounded (with temporary or permanent sequels) and material damage. Time is crucial in caring for victims of TA. There is a positive association between the delay of the rescue and the proportion of fatal and serious accidents. Several studies have demonstrated the relationship between the reduction in the time-response and the corresponding reduction of mortality. The time the succor leads to reach the victim is a most important variable in Prehospital Care (PHC). This time, known as time-response is a key performance indicator system. In this context, this paper analyzes the traffic accidents with victims occurred in the urban area of Uberlandia - MG, from January 1 to December 31, 2007, based on information generated by the reports of the 5th Battalion Military Fire. There are analyzed the month, the week, the day, the slots and areas more critical. With the TransCAD tools were done the characterization of the problem of transport, this work seeks optimal locations for the Care Units (CU) of Fire Department of Uberlandia, based on selected possible locations; to define routes for the preferential PHC from two scenarios. For each scenario were generated outputs in which there will be check the best settings of routes to the problem of rescuing the victims of traffic accidents. Even with some limitations of TransCAD in the search for solutions to the optimal pre-hospital care and routing of vehicles of rescue, this work contributed to reach the proposed objectives.